Entrepreneurial Knowledge and Learning Motivation as Predictors of Entrepreneurial Intention: The Mediating Role of Entrepreneurial Motivation - Bekti Utomo; Tri Wisudawati (Universitas Negeri Makassar, 2025)
Unemployment remains a persistent challenge in developing economies, making entrepreneurship an increasingly important pathway for job creation, economic participation, and student career development. This study examines the direct and indirect effects of entrepreneurial knowledge and learning motivation on entrepreneurial intention, with entrepreneurial motivation positioned as a mediating variable. Using a quantitative explanatory design, data were collected from 152 students of the Faculty of Economics and Business, Universitas Sebelas Maret, through a structured questionnaire and analyzed using descriptive statistics and path analysis with SPSS version 26. The findings show that learning motivation and entrepreneurial motivation have positive and significant effects on entrepreneurial intention, while entrepreneurial knowledge has a positive but statistically non-significant direct effect on entrepreneurial intention. Entrepreneurial knowledge and learning motivation were also found to have positive effects on entrepreneurial motivation, which subsequently strengthens students’ entrepreneurial intention. These results indicate that entrepreneurial intention is not shaped solely by cognitive understanding of entrepreneurship, but also by students’ motivation to learn and their internal motivation to engage in entrepreneurial activity. The study highlights the importance of entrepreneurship education that integrates knowledge development, motivational support, and practice-oriented learning experiences to strengthen students’ readiness to pursue entrepreneurship as a career option.